Factors Controlling the Development of Straight Valleys and Streams in the Kurdistan Region, North and Northeast of Iraq - Sissakian, Varoujan K.; Shihab, Ahmed T.; Othman, Arsalan A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
The Iraqi Kurdistan Region is a mountainous area with relief difference ranging from few hundred meters up to 3000 m, and locally more. Almost all of the mountains form anticlines that have NW–SE trend changing westwards of longitude to E–W. The carapace of the majority of the mountains is built up of Cretaceous rocks; however, some of them are of older rocks. Many of those anticlines are crossed by straight valleys and/or are crossed by streams and rivers which form again straight lines and almost coincide with regional lineaments, usually in N–S or NE–SW trend. The studied straight valleys are controlled, most probably by tectonic factors, therefore, exhibit special topographic forms, like straight lineaments crossing many successive anticlines, and also clear bending in some of the ridges in their crossing points to the valleys and/or streams. This paper aims to determine and discuss the factors that control the development of the straight valleys and/or lineaments. To achieve this aim, remote sensing and GIS techniques were followed, using Landsat, QuickBird images as well as geological maps of different scales, and different published articles.